Estimation of stature from foot anthropometry in Central Indian population - Karan Jain1 , Ninad Nagrale2 , Ranjit Ambad3 , Nandkishor Bankar4 , Swapnil Patond5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Out of many parameters for human identification, stature is a principal anatomical variable. Stature estimation,especially in post-mortem cases where only some parts of an individual is available or cases where onlyfootprints are available, foot anthropometry will be extremely useful. The objective of the current studyis to find out interrelationship between the stature & foot length & formulating a regression equation fordetermination of height from foot length among individuals from Central India. This cross sectional studywas conducted at the department of Forensic Medicine & Toxicology of Datta Meghe Medical College,Nagpur from June 2020 to August 2020. Collected data was entered in Microsoft Excel sheet & analysedusing SPSS software. Mean stature in male was 165.8 cm with SD of 6 cm, while in female, it was 159.9cm with SD of 6.7 cm. Gender wise difference in mean stature & foot length was statistically significant.This research found remarkable positive correlation between stature & foot-length in both sexes. Regressionformula was derived which will be extremely helpful to forecast the height of an individual from knownfoot-length in cases of medicolegal importance.